Respuesta :

First, recall some rules of exponents.

[tex] a^m * a^n = a^{m + n} [/tex]

[tex] \dfrac{a^m}{a^n} = a^{m - n} [/tex]

[tex] -a^n = - (a^n) [/tex]

[tex] a^{-n} = \dfrac{1}{a^n} [/tex]

Here is the solution.

[tex] \dfrac{-i^{-44} \cdot i^{35}}{i^8} = [/tex]

[tex] = -\dfrac{i^{-9} }{i^8} [/tex]

[tex] = -i^{-17} [/tex]

[tex] = -\dfrac{1}{i^{17}} [/tex]

[tex] = -\dfrac{1}{i} [/tex]

(For an explanation of how [tex] i^{17} [/tex] became [tex] i [/tex],
see below the final answer.)

[tex] = -\dfrac{1}{i} \times \dfrac{i}{i} [/tex]

[tex] = - \dfrac{i}{i^2} [/tex]

[tex] = \dfrac{-i}{-1} [/tex]

[tex] = i [/tex]

Final answer: [tex] i [/tex]



Integer powers of i.

[tex] i^0 = 1 [/tex]

[tex] i^1 = i [/tex]

[tex] i^2 = -1 [/tex]

[tex] i^3 = -1 \times i = -i [/tex]

[tex] i^4 = i^3 \times i = -i \times i = 1 [/tex] Notice that [tex] i^4 = i^0 [/tex]

Now the pattern is complete, and for each consecutive integer power, you get the same pattern of results. Let n be a positive integer multiple of 4.
Then,
i^n = 1
i^(n + 1) = i
i^(n + 2) = -1
i^(n + 3) = -i

After power n + 3, power n + 4 is again an multiple of 4, and you start again with 1. Notice that integer 17 is 16 + 1, so it is 1 more than a multiple of 4, so i^17 is the same as i^(n + 1) = i.
ACCESS MORE